Estudio de pre factibilidad para la implementación de una planta de tratamientos de aguas residuales en una Curtiembre de Trujillo - Correa Alayo, Vania Evelyn (2017)
The present research sought to determine the technical, economic and financial viability of the implementation of a wastewater treatment plant(PTAR) in a Trujillo tannery. For this, the following studies were carried out: strategic, market, technical, organizational and legal, economic and financial in the tannery company "León de Juda", evaluating wastewater during the years 2017-2021. The strategic analysis determined that the implementation of a PTAR through clean technologies is a strategy that will reduce production costs and generate greater profits. In the market study, the unsatisfied demand for the department of La Libertad was found, obtaining an average directed demand for the project of 59 thousand square feet per year in the next 5 years. In the technical study of the project, it was determined the work improvements in the salty will be reduced by 42% of salt used and the installation of the technology for the filtering and leaching of bath of hair, and the precipitate and redisolution of the tanning bath, achieving a reduction of 50% in sulfur, lime and water, and 41% of chromium; In addition to the implementation of a laboratory for strict control of the system. In the organizational and legal study, an efficient organizational design was made conformed by: 7 workers destined for the treatment plant of fur and tanning, and laboratory. In the economic and financial analysis, economic NPV of $ 76,701.92 was obtained, economic IRR of 38.35%, financial NPV of $ 82,004.83, financial IRR of 49.84%, economic recovery period of 2.81 years, and a financial recovery period of 2.34 years. Since the project is not sensitive to a variation of 20% of the parameters, it is concluded that the project is feasible technically, economically and financially.